The Impact of Solid State Transformers Integration on Frequency Stability - Chavez-Orostica, H; Fuentes-Parra, C (Institute of Electrical and Electronics Engineers Inc., 2021)
Load dynamics contributes to frequency stability by providing inertia, frequency response, and supporting system reserves. A future scenario of massive integration of Solid State Transformers may affect this contribution, as SSTs decouple the natural link between system frequency and load dynamics. This paper explores the effects of the Solid State Trans- formers integration in terms of frequency response. A load dynamics model is considered to represent the contribution of loads to frequency stability, and a simplified power system model is presented to assess the impacts. A simple feedback control for Solid State Transformers to provide frequency response is formulated to evaluate possible improvements and to obtain numerical results. © 2021 IEEE.
Keywords: Frequency control; Load modeling; Solid State Transformer